Loss of cytoplasmic KLF4 expression is correlated with the progression and poor prognosis of nasopharyngeal carcinoma. Issue 3 (12th June 2013) - Liu, Zhen; Yang, Huiling; Luo, Weiren; Jiang, Qingping; Mai, Chunping; Chen, Yan; Zhen, Yan; Yu, Xiaoli; Long, Xiaobin; Fang, Weiyi
Abstract : Aims: To examine, in nasopharyngeal carcinoma (NPC), the correlation of Krüppel‐like factor 4 (KLF4) expression with clinicopathological features including patient prognosis. Methods and results: Using real‐time PCR and immunohistochemistry, expression of KLF4 mRNA and protein was examined in NPC and nasopharyngeal tissues. The relationship of KLF4 expression levels with clinical features and prognosis of NPC patients was analysed. mRNA expression was markedly lower in NPC than in the nasopharyngeal tissues. Using immunohistochemistry, staining for KLF4 protein was found in the nuclei and cytoplasm of nasopharyngeal and malignant epithelial cells, but decreased cytoplasmic expression was observed in atypical hyperplasia and NPC samples compared to normal and squamous epithelium samples ( P < 0.001). In addition, levels of cytoplasmic KLF4 protein were correlated inversely with the nodal (N) status (TNM classification; P = 0.002) and overall clinical stage ( P < 0.001) of NPC patients. Patients with NPC showing lower cytoplasmic KLF4 expression had a significantly shorter overall survival time than those with high NPC KLF4 expression. Multivariate analysis suggested that the level of KLF4 expression was an independent prognostic indicator ( P = 0.008) for NPC survival. Conclusion: Low levels of cytoplasmic KLF4 expression are a potentially unfavourable prognostic factor for patients with NPC.